Psychological status of medical security teams in Winter Olympic Games and Paralympics under COVID-19 - Zhu, Xiaoyu; Zhu, Yu; Qi, Zhiwei; Li, Ran; Tan, Yunlong; Yang, Zhongwei (Frontiers in Public Health, 2024)
Background Medical security work for the 2022 Beijing Winter Olympic and Paralympics faced enormous challenges under COVID-19. This study aimed to investigate the mental status of those medical team members to provide a reference for scientifically implementing medical security services for large-scale events. Methods In this prospective cohort study, the Patient Health Questionnaire-9, Self-rating Anxiety Scale, General Self-Efficacy Scale, and Psychological Questionnaire for Emergent Events of Public Health (PQEEPH) were administered to 145 members of the medical team. A generalized mixed linear model was used to analyze the impact of work duration, position, on/off rotation, and gender on psychological status. Results Work duration significantly impacted depression, anxiety, self-efficacy, and all dimensions of PQEEPH. Women scored higher than men in the PQEEPH dimensions of depression, neurasthenia, fear, and total score. Working status affected the dimensions of depression, neurasthenia, and total score. Deterioration in emotional state became apparent in the fourth week and recovered 1 week after the task concluded, while self-efficacy decreased from beginning to end. Conclusion All the medical team members experienced emotional deterioration and decreased self-efficacy in medical security tasks. To maintain a medical team’s psychological wellbeing during large-scale activities, rotation times should be set reasonably, and adequate mental health services should be provided.